Tax Incentives and Taxpayer Compliance of Micro, Small and Medium Enterprises: The Moderating Role of Tax Literacy - Selviana Lelan Naitili; Atika Jauharia Hatta Hambali; Nurofik Nurofik (Journal of Economics, Business, and Accountancy Ventura, 2021)
The government's tax incentives for MSMEs during this pandemic are expected to increase taxpayer compliance. This study aims to provide empirical evidence of the effect of tax incentives during the COVID-19 pandemic on Micro, Small and Medium Enterprises (MSMEs) taxpayer compliance. This study also assesses the moderating influence of tax literacy on the relationship between tax incentives and taxpayer compliance. Using a sample of 108 MSME actors registered in the Yogyakarta Special Region of Cooperatives and MSMEs, the results indicate that tax incentives during the COVID-19 pandemic positively affect MSME taxpayer compliance. Meanwhile, tax literacy as a moderating variable weakens the impact of using tax incentives during the COVID-19 pandemic on MSME taxpayer compliance. The lack of tax literacy of MSME actors has resulted in the use of tax incentives being not optimal, so the government must increase the socialization of tax regulations to the public,Â especially among MSME actors.